(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
A fractal model for predicting the effective heat conductivity of fibrous assemblies was established. In the model, fiber-to-fiber contact influence on solid heat conductivity was taken into consideration. Radiative heat conductivity was also considered to get the effective heat conductivity. The effective heat conductivity was proved to be related to the following parameters, including the pore area fractal dimension, tortuosity fractal dimension, maximum and minimum pore diameters, solid conductivity, air conductivity, porosity and the ratio of the number of perpendicular channels to the total number of channels. Experiment was conducted to verify the model, and good agreement was found between the experimental and theoretical results.